The role of the United States of America in the African continent 2001. example) as an Africa North) 2016 (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The foreign policy of the United States of America towards many countries of the world is based on the principle of command and control and an attempt to exploit everything that can be exploited, whether through geographical location or through the natural resources and wealth found therein. This is the case with North Africa, which is rich in its wealth and natural resources, where The United States worked in all political, economic, social and cultural ways In order to control it to achieve its expansionist goals there, the previous and subsequent American administrations were making big plans to control the North African region, including the administration of former American President Bush Jr., especially after the events of September 11, as well as former President Barack Obama, who took advantage of the events in the Arab region. To achieve the goals of the American administration to control it.